Pemenuhan Pendidikan Terhadap Penyandang Disabilitas Berdasarkan International Covenant On Economic Social And Cultural Rights (ICESCR) Dan Convention Right Person Of Disabilities (CRPD) - Gultom, Rahel Elena (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2025)
Education is a fundamental human right and a key driver of social and economic development. Persons with disabilities often encounter barriers in accessing education, ranging from discrimination, inadequate facilities, and unprepared educators, to policies that are not fully inclusive. This research analyzes the fulfillment of the right to education for persons with disabilities based on the International Covenant on Economic, Social and Cultural Rights (ICESCR) and the Convention on the Rights of Persons with Disabilities (CRPD). Using normative legal research, this study examines the obligations of states under Articles 13 and 14 of ICESCR as well as Article 24 of CRPD, alongside Indonesia’s ratification through national legislation. The findings show that although Indonesia has adopted comprehensive legal frameworks, including Law No. 11 of 2005, Law No. 19 of 2011, and Law No. 8 of 2016, implementation remains challenged by limited resources, insufficient teacher training, and persistent stigma. This study suggests strengthening technical regulations, increasing budget allocation, and fostering public awareness to ensure inclusive education. The implications highlight the necessity of harmonizing international commitments with national policies to achieve substantive equality in education for persons with disabilities.